Фонетико-фонологические особенности стандартного шотландского варианта английского языка (SSE) в сравнении с британским произносительным стандартом (Received Pronunciation) - Евстафьева, Н.М. (Культура народов Причерноморья, 2014)
В статье проводится сравнительный анализ стандартного шотландского и английского вариантов произношения. В результате анализа выделяются основные фонетико-фонологические особенности шотландского вокализма и консонантизма. Некоторое совпадение с идиомом скотс на произносительном уровне свидетельствует о том, что шотландский вариант английского языка сформировался в результате фонетической интерференции. У статті проводиться порівняльний аналіз стандартного шотландського та англійського варіантів вимови. В результаті аналізу виділяються основні фонетико-фонологічні особливості шотландського вокалізму та консонантизму. Схожість з ідіомом скотс на вимовному рівні свідчить про те, що шотландський варіант англійської мови сформувався в результаті фонетичної інтерференції. The article describes the features of the Standard Scottish English (SSE) phonology contrastive to the phonology of the Received Pronunciation. It highlights the peculiarities of the “Scottish accent” and its main components. Special attention is given to the differences in the articulation of vowels and consonants in both variants. The vowel variation in SSE and SSBE and the influence of “r” on the preceding vowel is described partly using the pattern introduced by J. Scobbie. The two major linguistic factors influencing the spoken English in Scotland are the Estuary English (mainly from television) and the Scots language. Standard Scottish English is the variety of English that stands in between, therefore one of the most obvious ways of analyzing it for an outside observer it is to compare it with Standard English and Scots.